2020
DOI: 10.1111/codi.15055
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal bypass devices as an alternative to protective ostomy for prevention of colorectal anastomotic leakage: a systematic review of the literature

Abstract: Aim Anastomotic leakage (AL) is the most important complication of colorectal surgery, leading to high morbidity and mortality. Protective ostomy, the current standard of care for protecting a colorectal anastomosis, has important drawbacks that require the creation of an alternative strategy. Over the past 30 years, several intraluminal bypass devices, designed to shield the anastomosis from the faecal stream, have been developed. The aim of this literature review was to create an updated overview of the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…6 However, they have not been widely implemented in clinical practice mainly due to technical reasons, as described earlier by our research group. 6…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 However, they have not been widely implemented in clinical practice mainly due to technical reasons, as described earlier by our research group. 6…”
Section: Discussionmentioning
confidence: 99%
“…6 The potential benefit is the avoidance of the need for a protective ostomy and the associated drawbacks. 6 Previous studies with intraluminal bypass devices have demonstrated proof of concept in terms of efficacy, safety, and technical feasibility. 6 However, they have not been widely implemented in clinical practice mainly due to technical reasons, as described earlier by our research group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations